Pridnestrovian Migrant Workers in the Country of the Recipient: Quality of Life and Employment Features - Volkova, Olga А.; Ostavnaya, Alla N.; Besschetnova, Oksana V.; Kovalchuk, Olga V.; Bystriantsev, Sergei B. (Journal of History Culture and Art Research, 2017)
The article pays the attention to the role of Pridnestrovian migrants at the Russian labor market regarding the life’s quality, social interaction and employment. Authors think that migration policy of native and welcoming sides should be based on pragmatic approach when migrants’ labor should promote the development of human capital. Positive prerequisites of such process are social, demographic, professional, linguistic and cultural characteristics of Pridnestrovian migrants. The article contains the results of the survey of migrants (n=270), living in all regions of Pridnestrovie, conducted by the employees of the Pridnestrovie State University named after T.G. Shevchenko. The sample is formed based on heterogeneity of respondents and includes such criteria as gender, age, level of education, ethnicity and citizenship. The main emphasis in the research has been done on the study of the relationship of the following indicators: goals, quality of life, social relationships, and employment.